Science Learning Patterns for Primary School/ Madrasah Ibtidaiyah; Use of Circulatory Bottle Props on The Circulatory System - Nurdiansyah, Nana Meily; Jam'siawati, Dewi; Arief, Armai; Khaeroni, Khaeroni; Habudin, Habudin (Jurnal Basicedu, 2022)
One of the problems that often arises is the difficulty of Madrasah Ibtidaiyah teachers in conveying science concepts through life phenomena. The purpose of this study was to determine the pattern of learning by using the circulatory bottle as an aid to improve student learning outcomes. This research method uses descriptive qualitative and analytical techniques referring to the concept of Miles & Huberman with the research subject involving teachers, madrasah principals, and students of class V (five) MI Nurul Hasanah Sukaharja, totaling 23 students. The results of this study First, the learning pattern using the circulatory bottle props gave good results. Students look more active and enthusiastic than before. And make it easier for teachers to convey material to students because the material for the circulatory system is abstract material. Second, student learning outcomes show that there are differences in student learning outcomes between those who use teaching aids and those who do not. When the learning process takes place, students look enthusiastic and focus on paying attention to the teacher who is delivering the material. The circulatory bottle props can encourage students' creativity in asking questions, answering, justifying, and refuting inaccurate answers when discussing.